The empire of Manuel I Komnenos, 1143-1180 - Magdalino, Paul 1948- (Cambridge University Press, 1993)
The reign of Manuel I (1143–1180) marked the high point of the revival of the Byzantine empire under the Comnenian dynasty. It was, however, followed by a rapid decline, leading to the sack of Constantinople by the Fourth Crusade in 1204. This book, the first devoted to Manuel's reign for over eighty years, re-evaluates the emperor and his milieu in the light of recent scholarship. It shows that his foreign policy was a natural response to the western crusading movement and the expansionism of the German emperor Frederick Barbarossa. It also shows that what he ruled was more than the impoverished rump of a once great empire, or a society whose development had been arrested by a repressive regime. The twelfth century is presented here as a distinctive, creative phase in Byzantine history, when the empire maintained existing traditions and trends while adapting to a changing world